Penerapan Token Economy untuk Mengurangi Kecanduan Bermain Game Online Free Fire pada Anak SD - Suci Nurfadila; Nursamsiah Nursamsiah; Mutiara Murni; Rahmah Rezki Elvika (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
Online gaming addiction has become an increasingly widespread problem among children, having a negative impact on their development. The token economy technique is one behavior modification approach that is potentially effective in overcoming this problem. The aim of this research is to evaluate the effectiveness of applying the token economy technique in reducing the duration of playing online games and to analyze changes in children's behavior related to online game addiction This research method uses a single subject with an A-B research design, which consists of a baseline stage (A) and an intervention staged (B). Participants were 8 year old children who were diagnosed with online game addiction. Research subjects received training and application of token economic techniques for 1 week. Measurements were made for the duration of playing online games, changes in behavior related to addiction. The results showed that the subjects experienced a significant decrease in the duration of playing online games. Apart from that, there were more positive behavioral changes in the subjects, they experienced a decrease in playing time and became more responsive. These findings confirm the effectiveness of the token economy technique in modifying online game addiction behavior in children.